النمو السكاني في آراء ابن خلدون (Journal of the College of Basic Education, 2026)
This research discuss the views of the Arab philosopher Abdul Rahman Ibn Khaldun on population growth in the introduction to writing ( lessons and Diwan debutante and news in the days of the Arabs, non-Arabs, Berbers and their contemporaries with the greatest authority ) in 1377 AD in the light of modern demographic concepts, which is the first to write in the analysis of the relationship between the population , the economy and the state , Ibn Khaldun pointed out that population growth can not be separated from the economic and political conditions of the state is what leads to Reduce and increase the number of Population as a result of the spread of epidemics, unrest, poverty or migration , it is the main factor to development and establish the state, which is similar to what came by the modern population theories of Adam Smith , founder of the theory of human capital around the end and the theory of demographic transformation in the twentieth century .